2009
DOI: 10.1016/j.ejrad.2008.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of bacterial and non-bacterial community-acquired pneumonia by thin-section computed tomography

Abstract: Thin-section CT examination was applied for the differentiation of bacterial and non-bacterial pneumonias. Though showing some potential, this examination at the present time would not be applicable for patients with underlying lung diseases, severe conditions of pneumonia, or immunocompromised conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…One prospective study of community-acquired pneumonia demonstrated that thin-section CT could differentiate bacterial pneumonia from nonbacterial lung disease with reasonable accuracy but only in patients without underlying lung disease. 19 Therefore, we think CT should not be recommended for initial evaluation of patients with pneumonia because of radiation exposure, although CT can be helpful in complicated cases to characterize overlapped pneumonia, to look for complications, or to detect underlying diseases in the lungs and mediastinum.…”
Section: Discussionmentioning
confidence: 98%
“…One prospective study of community-acquired pneumonia demonstrated that thin-section CT could differentiate bacterial pneumonia from nonbacterial lung disease with reasonable accuracy but only in patients without underlying lung disease. 19 Therefore, we think CT should not be recommended for initial evaluation of patients with pneumonia because of radiation exposure, although CT can be helpful in complicated cases to characterize overlapped pneumonia, to look for complications, or to detect underlying diseases in the lungs and mediastinum.…”
Section: Discussionmentioning
confidence: 98%
“…More minute findings can be recognized on chest CT, which can help to differentiate the pathogens that cause pneumonia. In addition, chest CT can confirm the existence of cavitations or other complications (5,8).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike chest radiography, chest CT provides cross-sectional images; therefore, the pattern of pulmonary pathology distribution can be appreciated more readily with chest CT than with conventional radiology (6,7). It has been reported that there are few characteristic features indicative of causative organisms (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…No significant differences were observed between MS patients and MR patients. When we judged M. pneumoniae pneumonia as showing radiographic features with the combination of bronchial wall thickening and centrilobular nodules and/or ground-glass attenuation with lobular distribution (15,16), the diagnostically significant findings for suspecting M. pneumoniae pneumonia were found in 69% of MS patients and 70% of MR patients.…”
mentioning
confidence: 99%